Short Communication: Species identity and taxonomical position of selected species of Annonaceae based on trnL molecular marker - DEWI AYU LESTARI; RODIYATI AZRIANINGSIH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Lestari DA, Azrianingsih R. 2019. Species identity and taxonomical position of selected species of Annonaceae based on trnL molecular marker. Biodiversitas 20: 1012-1019. Identification based on morphological characters could be difficult when some characters are not visible. The absence of some morphological characters could effect for identification of species identity and taxonomical position of the species. Confirmation by the DNA data is needed to support species identification. The sequence was used in this research is trnL intron as non-coding sequence DNA, based on chloroplast DNA. The research aimed to estimate of species identity and determine of taxonomical position of species of Annonaceae based on trnL sequences. Methods were used through steps of DNA extraction, DNA amplification, DNA sequencing, and data analysis to selected species of Annonaceae from Purwodadi Botanic Garden (PBG), the trnL intron sequences of 10 Annonaceae species from GenBank database and two species of Magnoliaceae as out-group. Results showed that trnL sequence as non-coding gene explains the different groupings with the previous groupings in Annonaceae to this observed species. trnL sequence can estimate of species identity as much as 30%, caused by changes of nucleotide bases from mutation and missing data. Polymorphism of DNA sequences showed that 61.18% sites as conserved region, 24.05% sites as polymorphic variation and 14.76% sites as alignment gaps. Oxymitra sp. is in group (monophyletic) with Mitrephora javanica because they are genetically in close relationship (Uvariae tribes and Annonoideae sub-family), Popowia sp. is in group with Orophea enterocarpa, because they are genetically in close relationship (Miliuseae tribes and Malmeoideae sub-family).